Association Between Alleles of the Waxy Gene and Traits of Grain Quality in Philippine Seed Board Rice Varieties - Roferos, Leslie T. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2008)
The association between alleles of the Waxy gene, defined by the number of CT repeats on exon 1, and traits of grain quality was carried out using 47 Philippine Seed Board rice varieties. The major alleles of the Waxy gene in the set of 47 were (CT)10, (CT)11, (CT)17 and (CT)20. Varieties were divided into four clusters based on the metric of each trait of grain quality. (CT)10 (27-32% amylose content (AC)) and (CT)11 (22-30% AC) were mainly in clusters 3 and 4 (hard texture), and (CT)17 (20-24% AC) and (CT)20 (18-27% AC) were exclusively in grain quality cluster 1 (soft texture) and 2 (medium texture). (CT)n associated negatively with AC in this set. Only six (CT)11 and one (CT)10 rices were in cluster 4 (high-AC low-GT) and had high RVA consistency (final viscosity – trough viscosity) > 200 RVU. (CT)17 seemed to be the preferred source of low-intermediate AC in the Philippine rice breeding program, followed by (CT)20.